2021
DOI: 10.1167/jov.21.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Translucency perception: A review

Abstract: Translucency is an optical and a perceptual phenomenon that characterizes subsurface light transport through objects and materials. Translucency as an optical property of a material relates to the radiative transfer inside and through this medium, and translucency as a perceptual phenomenon describes the visual sensation experienced by humans when observing a given material under given conditions. The knowledge about the visual mechanisms of the translucency perception remains limited. Accurate prediction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 135 publications
1
38
0
Order By: Relevance
“…By manipulating the weights of the image features listed by Beurs -highlights, edge reflections, and bloom -Di Cicco et al (2020a) inferred a causal relationship with the perception of the material properties glossiness, translucency, and bloom. The highlights were used as perceptual cues for glossiness and translucency perception, in agreement with the literature (Chadwick and Kentridge, 2015;Fleming and Bülthoff, 2005), and the edge reflections also increased the translucent appearance, again in agreement with literature about the cues for translucency (Fleming and Bülthoff, 2005;Gigilashvili et al, 2021;Gkioulekas et al, 2015;Nagai et al, 2013;Wijntjes et al, 2020;Xiao et al, 2020), whereas the image feature of the bloom was the direct trigger of bloom perception. Di Cicco et al (2019) further showed that the glossiness of grapes is predicted by high contrast, blurry highlights, in agreement with Beurs' instructions.…”
Section: An Index Of Key Features For Materials Perceptionsupporting
confidence: 84%
“…By manipulating the weights of the image features listed by Beurs -highlights, edge reflections, and bloom -Di Cicco et al (2020a) inferred a causal relationship with the perception of the material properties glossiness, translucency, and bloom. The highlights were used as perceptual cues for glossiness and translucency perception, in agreement with the literature (Chadwick and Kentridge, 2015;Fleming and Bülthoff, 2005), and the edge reflections also increased the translucent appearance, again in agreement with literature about the cues for translucency (Fleming and Bülthoff, 2005;Gigilashvili et al, 2021;Gkioulekas et al, 2015;Nagai et al, 2013;Wijntjes et al, 2020;Xiao et al, 2020), whereas the image feature of the bloom was the direct trigger of bloom perception. Di Cicco et al (2019) further showed that the glossiness of grapes is predicted by high contrast, blurry highlights, in agreement with Beurs' instructions.…”
Section: An Index Of Key Features For Materials Perceptionsupporting
confidence: 84%
“…Translucency is defined as the ability of a substance to pass through the light and is in between a range from complete opacity to transparency [ 10 ]. Another property which is inversely related to translucency is masking ability.…”
Section: Introductionmentioning
confidence: 99%
“…By breaking the spatial consistency, some highlights look like albedo changes by white paint ( Beck & Prazdny, 1981 ; Kim et al., 2011 ; Marlow et al., 2011 ; Sawayama & Nishida, 2018 ). In addition to gloss perception, translucency perception has also been widely investigated ( Fleming & Bülthoff, 2005 ; Motoyoshi, 2010 ; Gkioulekas, Xiao, Zhao, Adelson, Zickler, & Bala, 2013 ; Nagai, Ono, Tani, Koida, Kitazaki, & Nakauchi, 2013 ; Xiao et al., 2014 ; Chadwick, Cox, Smithson, & Kentridge, 2018 ; Gigilashvili, Thomas, Hardeberg, & Pedersen, 2021 ). We adopted the task of discriminating opaque from translucent objects by controlling the thickness of the translucent media ( Figure 1 , task 3).…”
Section: Introductionmentioning
confidence: 99%